Biography and its historians in Medina in the first and second centuries AH | علم السيرة ومؤرخوها في المدينة المنورة في القرنين الأول والثاني الهجريين - Nour | نور, Yasser Ahmed | ياسر أحمد (Al-Madinah Al-Munawwarah Research and Studies Center | مركز بحوث ودراسات المدينة المنورة, 2023)
Research topic: pp. 165-238 | موضع البحث: ص 165 - 238